El entorno social y el desarrollo del lenguaje en los niños de 5 años de la unidad educativa experimental anexa a la Universidad Nacional de Loja - Valdivieso Flores, Mayra Alejandra (2014)
Investigated how the social environment affects language development of children of 5 years in the Experimental Education Unit Attached to the National University of Loja? Likewise, the hypothesis that guided the research process was: The social environment influences language development of children of 5 years in the Experimental Education Unit Attached to the National University of Loja. The work was conducted in the period between March and June 2013, on the premises of that educational unit, county and province of Loja. For the preparation of this research, report used the following methods: scientific, systemic analytical, inductive and deductive hypothetical, who helped with the development of this thesis, also used techniques such as surveys aimed at parents in order to know the social environment of their children, and an interview guide aimed at teachers for language development in children. Once ordered, processed and analyzed the data, it was concluded that if there is significant difference in language development among children who come from socially stable compared with those from unstable social environments. This analyzed by Student's t test at 95% probability. After analysis of the information obtained leads to the conclusion that if the social environment influences the development of language in children 5 years Education Unit Attached to the National University of Loja.